Novel coumarin-6-sulfonamide-chalcone hybrids as glutathione transferase P1-1 inhibitors - Sabt, Ahmed; Kitsos, Stefanos; Ebaid, Manal S; Furlan, Veronika; Pantiora, Panagiota D; Tsolka, Magdalini; Elkaeed, Eslam B; Hamissa, Mohamed Farouk; Angelis, Nikolaos; Tsitsilonis, Ourania E; Papageorgiou, Anastassios C; Bren, Urban; et al. (PloS one, 2024)
Multidrug resistance (MDR) mechanisms in cancer cells are greatly influenced by glutathione transferase P1-1 (hGSTP1-1). The use of synthetic or natural compounds as hGSTP1-1 inhibitors is considered an effective approach to overcome MDR. Nine compounds consisting of coumarin-6-sulfonamide linked to chalcone derivatives were synthesized and evaluated for their ability to inhibit hGSTP1-1. Among the synthetic derivatives, compounds 5g, 5f, and 5a displayed the most potent inhibitory effect, with IC50 values of 12.2 ± 0.5 μΜ, 12.7 ± 0.7 and 16.3 ± 0.6, respectively. Kinetic inhibition analysis of the most potent molecule, 5g, showed that it behaves as a mixed-type inhibitor of the target enzyme. An in vitro cytotoxicity assessment of 5a, 5f, and 5g against the human prostate cancer cell lines DU-145 and PC3, as well as the breast cancer cell line MCF-7, demonstrated that compound 5g exhibited the most pronounced cytotoxic effect on all tested cell lines. Molecular docking studies were performed to predict the structural and molecular determinants of 5g, 5f, and 5a binding to hGSTP1-1. In agreement with the experimental data, the results revealed that 5g exhibited the lowest docking score among the three studied inhibitors as a consequence of shape complementarity, governed by van der Waals, hydrogen bonds and a π-π stacking interaction. These findings suggest that coumarin-chalcone hybrids offer new perspectives for the development of safe and efficient natural product-based sensitizers that can target hGSTP1-1 for anticancer purposes.
Keywords: chalkon; MFC-7 buňky; Humans; simulace molekulového dockingu; Glutathione S-Transferase pi; Molecular Docking Simulation; sulfonamidy; Antineoplastic Agents; kumariny; glutathion-S-transferasa fí; lidé; Chalcones; Coumarins; nádorové buněčné linie; protinádorové látky; inhibitory enzymů; Chalcone; chalkonoidy; Cell Line, Tumor; Enzyme Inhibitors; Sulfonamides; MCF-7 Cells